Studi Tematik Hadis Tentang Mahar dan Budak dalam Tinjauan Syar’i - Shohibul Umam; Hafidz Taqiyuddin (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
Dowry and slaves are two different things. Mahar is property or something given by a husband to his wife as part of their marriage. This is supported by a hadith from Muhammad Shallallahu 'Alaihi wa Sallam which says "Marry a woman with a dowry even if it's only a piece of egg." (Narrated by Bukhari). Meanwhile, slaves are human beings who are the same as other people and have rights that must be respected. There are several hadiths from Muhammad Shallallahu 'Alaihi wa Sallam which emphasizes protection for slaves. One example is "Indeed Allah Subhanahu wa Ta'ala will empower three people: a young man who is given an advantage by Allah in worship, a man who donates alms in secret so that his left hand does not know what his right hand is doing, and a slave owner who are honest and treat them well." (Narrated by Bukhari). This shows that slaves must be treated fairly and well by their employers and must not be seen as merchandise or exploited to work without pay.